Designing Networked Improvement in a Small‐College Context. Issue 173 (July 2017) - Rachford, Jennifer L.; Brown, Travis M.; Sambolin, Hector L.; Seligman, Lenny
Abstract : This chapter demonstrates the complexity of pedagogical and curricular change as it unfolds through several overlapping phases of increasingly coordinated reflection and action around STEM initiatives at Pomona College. It argues for a networked model of research and practice, drawing on theory and lessons from improvement science and highlighting the role of institutional research in supporting change initiatives.